La commercialité des immeubles : une théorie en construction - Antaki, Nabil (Les Cahiers de droit, 1978)
Until recently, the rule in Quebec was that an immoveable could not be the object of a commercial operation. For many years, this anachronic rule had major effects on a number of key sectors of the law. Although unanimously criticised by academics, it was still largely applied by the courts. In 1965, a new trend appeared with the key decision of Colonia Development v. Belliveau, according to which the Court of Appeal departed for the first time from the traditional pattern, applying a new test wholly based on the purpose of the parties in entering into the agreement and refraining, by the same way, from holding that contracts in respect to immoveables were per se a civil matter. Three recent decisions of the Court of Appeal confirmed this precedent and applied it to situations involving different aspects of immoveable transactions. These decisions repeatedly adopted the purpose test definitely prefering the subjective approach to commercial activities over the objective one. This settled another important controversy between academics. After a general review of the situation since the Colonia Development case, the article spots a new dark area in the field and tries to draw a new line between civil and commercial transactions, especially when an immoveable is concerned.